(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present research was designed to evaluate the cardio-protective role of chronic oral administration of Hibiscus syriacus flower extract against Isoproterenol-induced myocardial injury in rats and to compare it with α-tocopherol, a known cardioprotective antioxidant. Male Wistar albino rats were randomly divided into five groups (n = 6) and treated as per treatment protocol with two different doses of Hibiscus syriacus Methanolic extract (250 and 500 mg/kg body weight) 6 days per week for 4 weeks. At the end of the treatment, all the rats (except control rats) were administered with Isoproterenol (85 mg/kg) for two consecutive days and subjected to biochemical and histopathological estimation. Isoproterenol (group II) induced oxidative myocardial damage via alteration in the endogenous antioxidant enzymes and myocardial marker enzymes. Hibiscus syriacus extract in all two doses (group III, and IV) shows a protective mechanism via decreasing thiobarbituric acid reactive substance (TBARS) and enhancing the endogenous antioxidant enzymes (reduced glutathione (GSH), superoxide dismutase (SOD), and catalase). In Hibiscus syriacus treated groups significant increase (p<0.001) of LDH in heart homogenate and a decrease of SGOT and LDH in serum were observed. Microscopic studies in ISO-treated animals revealed mitochondrial swelling, leukocyte infiltration, lipid inclusions, and myofibrillar loss whereas the pre-treatment with Hibiscus syriacus led to a lesser degree of ISO-induced histological alterations. The extract effect was compared with the reference standard α‑tocopherol which also offered similar protection in biochemical and histopathological changes. Thus, the study shows that Hibiscus syriacus Methanolic extract exhibits significant antioxidant activity and protects the heart from free radical-mediated toxicity of Isoproterenol.